Implications for public health research of models and theories of disability: a scoping study and evidence synthesis - Maria Berghs; Karl Atkin; Hilary Graham; Chris Hatton; Carol Thomas (NIHR Journals Library, 2016)
Background: Public health interventions that are effective in the general population are often assumed to apply to people with impairments. However, the evidence to support this is limited and hence there is a need for public health research to take a more explicit account of disability and the perspectives of people with impairments. Objectives: (1) To examine the literature on theories and models of disability; (2) to assess whether or not, and how, intervention studies of effectiveness could incorporate more inclusive approaches that are consistent with these theories and models; and (3) to use the findings to draw out implications for improving evaluative study designs and evidence-based practice. Review methods: The project is a scoping review of the literature. The first stage examines theories and models of disability and reflects on possible connections between theories of disability and public health paradigms. This discussion is used to develop an ethical-empirical decision aid/checklist, informed by a human rights approach to disability and ecological approaches to public health. We apply this decision aid in the second stage of the review to evaluate the extent to which the 30 generic public health reviews of interventions and the 30 disability-specific public health interventions include the diverse experiences of disability. Five deliberation panels were also organised to further refine the decision aid: one with health-care professionals and four with politically and socially active disabled people. Results: The evidence from the review indicated that there has been limited public health engagement with theories and models of disability. Outcome measures were often insensitive to the experiences of disability. Even when disabled people were included, studies rarely engaged with their experiences in any meaningful way. More inclusive research should reflect how people live and 'flourish' with disability. Limitations: The scoping review provides a broad appraisal of a particular field. It generates ideas for future practice rather than a definite framework for action. Conclusions: Our ethical-empirical decision aid offers a critical framework with which to evaluate current research practice. It also offers a resource for promoting more ethical and evidence-based public health research that is methodologically robust while being sensitive to the experiences of disability. Future work: Developing more inclusive research and interventions that avoid conceptualising disability as either a 'burden' or 'problem' is an important starting point. This includes exploring ways of refining and validating current common outcome measures to ensure that they capture a diverse range of disabling experiences, as well as generating evidence on meaningful ways of engaging a broad range of disabled children and adults in the research process. Funding: The National Institute for Health Research Public Health Research programme.